Physicochemical and sensory characteristics of fine sparkling red wines produced at different maceration lengths in the south of Brazil (Bioscience Journal, 2018)
Maceration is the step of the vinification process in which phenolic and aromatic compounds are transferred to wine. This study aimed at producing fine sparkling red wines by testing different grape varieties and maceration lengths. Grapes underwent maceration for 24 hours (Very Short Maceration - VSM) and for 48 hours (Short Maceration - SM). Sparkling wines were produced by the traditional method and analyses were carried out in the must, base wines and sparkling wines. Analyzes of minerals, volatile compounds and physicochemicals related to total soluble solids (TSS), Volatile Acidity (VA); Free Sulfur Dioxide (Free SO2); Total Sulfur Dioxide (Total SO2); Total Titratable Acidity (TTA); Fixed Acidity (FA); Hydrogenionic Potential (pH); Alcoholic Content (AC); Reduced Dry Extract (RDE); Total Tannins (TT); Total Anthocyanins (TA); Total Polyphenol Content (TPC); Total Color Intensity (TCI). In addition, during the tasting, a quantitative and descriptive record was distributed to the researchers to characterize the wines in relation to color, perlage, aroma, flavor, main descriptor of the aroma and main general adjective. The sparkling wines which had the best evaluations at different maceration lengths were the following: sparkling wine 100% Teroldego (SM) and sparkling wine 62.5% Teroldego, 18.75% Merlot and 18.75% Pinot (SM). Both short maceration (48 hours) and the Teroldego variety were the vinification parameters which provided the best olfactory-gustatory and color characteristics to the sparkling wines under study. All sparkling wines had enological potential to be vinified in red. Maturation and maceration processes under evaluation produced the typical freshness of sparkling wines and the desired red color.